Physical fitness, balance and falls in older adults - Loureiro, Vânia (2019)
Aim. Falls are the second leading cause of accidental injury and deaths worldwide. Individuals aged 65 or above have the highest rates. Falls are preventable, but the consequences of falls can lead to injuries and may result in loss of independence. The present study aims to analyse the relationship between risk of falls, physical activity level (PA level) and physical fitness among elderly practitioners of physical exercise interventions. Basic procedures. The data were collected through a demographic questionnaire; history of falls; PA level and physical fitness. Statistical analysis was performed using IBM® SPSS®, version 24.0 for Windows (p 0.05). Main findings. The study comprised 62 seniors taking part in physical exercise programmes from the community of Beja, Portugal (females n = 48; 77.4%), with the average age of 73.27 ± 5.45 years. Results. It was found that elderly people with lower levels of strength, balance and cardiorespiratory fitness are at a higher risk of falls (p<0.05). There were no correlations between the risk of falls and the PA level. Conclusion. The results highlight the need for more specific research about strength and balance interventions in older adults reporting falls, in particular, the identification of intrinsic and extrinsic risk factors for their prevention.